2022
DOI: 10.1021/jacs.2c07575
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processable Redox-Active Polymers of Intrinsic Microporosity for Electrochemical Energy Storage

Abstract: Redox-active organic materials have emerged as promising alternatives to conventional inorganic electrode materials in electrochemical devices for energy storage. However, the deployment of redox-active organic materials in practical lithium-ion battery devices is hindered by their undesired solubility in electrolyte solvents, sluggish charge transfer and mass transport, as well as processing complexity. Here, we report a new molecular engineering approach to prepare redox-active polymers of intrinsic micropor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Sequentially, lithium atoms were then placed at different active sites of Alkynyl-CPF and the optimized geometries (Figure 5c) were obtained by simulations. [29] Combined with Figure 5a, it can be clearly observed that the site near C=N units of phenanthroline exhibits the most negative state and accepts 6 Li atoms (ΔE ad = À 0.43 eV) for each unit, indicating its strongest affinity for cations (such as Li + ) due to its higher electronegativity of N than C atoms. Then, the active sites of C�C bonds show a much negative value through the whole conjugated structure.…”
Section: Forschungsartikelmentioning
confidence: 61%
“…Sequentially, lithium atoms were then placed at different active sites of Alkynyl-CPF and the optimized geometries (Figure 5c) were obtained by simulations. [29] Combined with Figure 5a, it can be clearly observed that the site near C=N units of phenanthroline exhibits the most negative state and accepts 6 Li atoms (ΔE ad = À 0.43 eV) for each unit, indicating its strongest affinity for cations (such as Li + ) due to its higher electronegativity of N than C atoms. Then, the active sites of C�C bonds show a much negative value through the whole conjugated structure.…”
Section: Forschungsartikelmentioning
confidence: 61%
“…To further explore the porosity of CPTA, the CO 2 (Figure 2h) adsorption–desorption method was applied as well. [ 42 ] As for CPTA, the CO 2 adsorption–desorption plots give a higher SSA of 130 m 2 g −1 with an average pore size of ≈0.5 nm (the inset in Figure 2h), indicating the domination of the micro‐pore structure in CPTA. The trimodal pores (i.e., macro‐/meso‐/micro‐) co‐existing in CPTA are favorable for exposing more electroactive sites, [ 43 ] boosting the ions/electrolyte transfer, and accommodating the volume expansion during cycling, [ 44–46 ] which can effectively enhance the Na‐storage capacity, cycling stability, and electrochemical kinetics for SIBs.…”
Section: Resultsmentioning
confidence: 97%
“…[21][22][23] The linker exchange approach is an effective approach for transforming amorphous covalent organic polymers (COPs) into highly crystalline COFs; therefore, can aid in accessing optimized materials for electrochemical energy storage. [24][25][26][27][28][29] Extending this approach to porous polyimides Scheme 1. Conventional synthetic route and the alternative linker exchange approach for a crystalline porous polyimide framework synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21–23 ] The linker exchange approach is an effective approach for transforming amorphous covalent organic polymers (COPs) into highly crystalline COFs; therefore, can aid in accessing optimized materials for electrochemical energy storage. [ 24–29 ] Extending this approach to porous polyimides holds great promise, especially in advanced rechargeable lithium and sodium‐ion batteries wherein rapid ion and charge transfer and full accessibility of the redox‐active sites dictate device performance. [ 30–33 ] Such properties become even more crucial when sodium is employed because of its large ionic size and sluggish intercalation kinetics.…”
Section: Introductionmentioning
confidence: 99%